SPINAL DISC HERNIATION L4-S1 WITH CHRONIC EROSIVE GASTRITIS - Hema Anggika Pratami (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2015)
Spinal disc herniation or called HNP is exploited nucleus pulposus into the vertebral canal due to degeneration of the annulus fibrosus of vertebra corpus caused by degenerative process and traumatic, while gastritis is an inflammation of the lining of the stomach mucosa and submucosa. A female, 55 years old, came to Abdul Moeloek Hospital in Bandar Lampung with complaint of low back pain that radiates down to the legs and feet, especially the left side since one year ago. A history of vomiting blood andstool black as asphalt one year ago. The physical examination found positive test Lasseque right and left, a positive test Kernig right and left. Achilles tendon reflex left leg negative. Examination Patrick and counter Patrick positive on the right and left leg. Hipoestesi obtained from the calf to the left foot. Tenderness in the epigastrium. Has been performed endoscopy in patient, the result was erosive gastritis. The diagnosis of this patient is spinal disc herniation and chronic erosive gastritis. The management to this patient was paracetamol 500 mg 3x1 tablet, omeprazole tablets 20 mg 2x1, sucralfate 3x1 table spoon syrup, and vitamin B complex tablets 2x1. Then planned for laminectomy surgery. [J Agromed Unila 2015; 2(1):13-17]Keyword: chronic erosive gastritis, low back pain, spinal disc herniation